Bioactive Glass Fiber-Reinforced PGS Matrix Composites for Cartilage Regeneration - Trevelin Souza, Marina; Tansaz, Samira; Dutra Zanotto, Edgar; Boccaccini, Aldo R. (Materials, 2017)
Poly(glycerol sebacate) (PGS) is an elastomeric polymer which is attracting increasing interest for biomedical applications, including cartilage regeneration. However, its limited mechanical properties and possible negative effects of its degradation byproducts restrict PGS for in vivo application. In this study, a novel PGS–bioactive glass fiber (F18)-reinforced composite was developed and characterized. PGS-based reinforced scaffolds were fabricated via salt leaching and characterized regarding their mechanical properties, degradation, and bioactivity in contact with simulated body fluid. Results indicated that the incorporation of silicate-based bioactive glass fibers could double the composite tensile strength, tailor the polymer degradability, and improve the scaffold bioactivity.
Keywords: poly(glycerol sebacate); bioactive glass; fibers; composite; cartilage; tissue engineering

Biomedical applications of soy protein: A brief overview - Tansaz, Samira; Boccaccini, Aldo R. (Journal of Biomedical Materials Research Part A, 2016)
Soy protein (SP) based materials are gaining increasing interest for biomedical applications because of their tailorable biodegradability, abundance, being relatively inexpensive, exhibiting low immunogenicity, and for being structurally similar to components of the extracellular matrix (ECM) of tissues. Analysis of the available literature indicates that soy protein can be fabricated into different shapes, being relatively easy to be processed by solvent or melt based techniques. Furthermore soy protein can be blended with other synthetic and natural polymers and with inorganic materials to improve the mechanical properties and the bioactive behavior for several demands. This review discusses succinctly the biomedical applications of SP based materials focusing on processing methods, properties and applications highlighting future avenues for research.
Keywords: drug delivery systems; plant-derived protein; soy protein isolate; tissue engineering; wound dressing

Hydrogel films and microcapsules based on soy protein isolate combined with alginate - Tansaz, Samira; Durmann, Ann-Katrin; Detsch, Rainer; Boccaccini, Aldo R. (Journal of Applied Polymer Science, 2016)
Alginate hydrogels are combined with soy protein isolate (SPI), a plant derived protein with low immunogenicity, appropriate biodegradability and low cost, to produce biocompatible films, and microcapsules. The cell–material interaction is assessed through the use of mouse embryotic fibroblast cells (MEF cells) on films, and the results illustrate that the alginate/SPI hydrogel films support cell attachment, spreading, and proliferation. Cell biology results combined with degradation studies suggest that such hydrogels are promising biomaterials for soft tissue regeneration or as wound dressing materials.
Keywords: alginate; biomedical applications; hydrogels; soy protein isolate

Micropatterned Down-Converting Coating for White Bio-Hybrid Light-Emitting Diodes - Niklaus, Lukas; Tansaz, Samira; Dakhil, Haider; Weber, Katharina; Pröschel, Marlene; Lang, Martina; Kostrzewa, Monika Maria; Coto, Pedro B.; Detsch, Rainer; Sonnewald, Uwe; Wierschem, Andreas; Boccaccini, Aldo R.; et al. (Advanced Functional Materials, 2017)
White hybrid light-emitting diodes (WHLEDs) are considered as a solid approach toward environmentally sustainable lighting sources that meet the "Green Photonics" requirements. Here, WHLEDs with protein-based down-converting coatings, i.e., Bio-WHLEDs, are demonstrated and exhibit worthy white color quality, luminous efficiency, and stability values. The coatings feature a multilayered cascade-like architecture with thicknesses of 1-3 mm. This limits the efficiency due to the low optical transmittance. Thus, submillimeter coatings, where the location of the proteins is well-defined, are highly desired. It is in this context where the thrust of this work sets in. Here, a straightforward way to design microstructured single-layer coatings, in which the proteins are placed at our command by using 3D printing, is presented. Based on comprehensive spectroscopic and rheological investigations, the optimization of the matrix and the plotting to prepare different micropatterns, i.e., lines, open-grids, and closed-grids, is rationalized. The latter are applied to prepare Bio-WHLEDs with approximate to 5-fold enhancement of the luminous efficiency compared to the reference devices with a cascade-like coating, without losing stability and color quality. As such, this work shows a new route to exploit proteins for optoelectronics, setting a new avenue of research into the emerging field of Bio-WHLEDs.

Novel electrospun poly(glycerol sebacate)-zein fiber mats as candidate materials for cardiac tissue engineering - Dippold, Dirk; Tallawi, Marwa; Tansaz, Samira; Roether, Judith; Boccaccini, Aldo R. (European Polymer Journal, 2016)
The application of a cardiac patch made of biodegradable polymer is a novel approach in regenerative therapies for infarcted cardiac tissue and aims to deliver healthy and functional cells on a mechanically supporting matrix to the damaged area of the myocardium. In this study a novel type of tissue engineered cardiac construct based on poly(glycerol sebacate) (PGS) blended with the corn protein zein was developed. Bead free electrospun PGS-zein fibers were fabricated using acetic acid as a benign solvent. In vitro degradation studies in PBS revealed a physicochemically stable system over a 28 day period showing only a slight drop in pH after 28 days. The results indicate that the novel PGS-zein fibrous structures are attractive biomaterials which can be valuable for cardiac patch applications thus warranting their further investigation in vitro and in vivo.
Keywords: Cardiac tissue engineering; Electrospinning; Poly(glycerol sebacate); Zein

Printing Wearable Devices in 2D and 3D: An Overview on Mechanical and Electronic Digital Co-design - Tansaz, Samira; Baronetto, Annalisa; Zhang, Rui; Derungs, Adrian; Amft, Oliver (IEEE Pervasive Computing, 2019)
Multiprocess Additive Manufacturing (AM) offers system designers new, exciting computational tools to rapidly realise smart wearable sensing devices in two-dimensional (2D) and 3D shapes. We guide readers through the novel development and fabrication process based on a digital co-design framework and highlight AM techniques, functional materials, and assembly procedures for designing wearables as flexible and stretchable on-skin patches, e-textiles, and smart accessories for everyday use.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Fabrication; Ink; Printing; Substrates; Three-dimensional displays; Tools; Two dimensional displays

Soja-Protein-basierte Biomaterialien für Weichgewebezüchtung und Wundversorgung - Tansaz, Samira (2017)
Biomaterials have been utilized in tissue engineering and regenerative medicine as synthetic or natural derived scaffolds to support cells in order to promote tissue regeneration and to restore the function of injured tissue. Different biomaterials chosen for scaffold fabrication may contain however some unfavorable properties. In order to bypass some of the limitations of synthetic polymers such as having undesirable degradation products and being inactive or, moreover, to tackle potential biocompatibility issues with animal derived proteins like immunogenicity, this project investigated soy protein isolate (SPI) as a green and abundant plant derived protein in a variety of structures for soft tissue engineering and wound dressing applications. Composite SPI films containing bioactive glasses (BG) showed hemostatic capability which is important for wound healing applications. Moreover, cell culture study results confirmed attachment, spreading and proliferation of mouse embryonic fibroblast (MEF) cells on these composite films, particularly for SPI films containing 13-93 BG that could be due to the smoother surface morphology of this film in comparison to other composite films fabricated with other BG composition. In order to suggest SPI based hydrogels for other types of wounds like diabetic ulcers or burn wounds, SPI was combined with alginate which is a well-known hydrogel that has been used for decades as wound dressing material. Alginate (Alg) has some drawbacks such as slow and uncontrolled degradation and poor cell adhesion properties which was solved in the present study by blending with SPI. Cytocompatibilty results of 2D cell culture on Alg/SPI hydrogels showed better cell attachment and proliferation for both human umbilical vein endothelial cells (HUVEC) and normal human dermal fibroblast (NHDF) cells compared to pure alginate hydrogel films. The addition of BG also promoted cell attachment and proliferation which might be due to changes in the surface morphology of the hydrogels and ionic dissolution products of BG. Nano indentation outcomes on Alg/SPI hydrogel films indicated higher effective Young’s modulus in comparison to pure Alg hydrogel films. As a 3D model, encapsulated human adipose-derived mesenchymal stem cells (hADSCs) in Alg/SPI hydrogel microcapsules indicated migration and proliferation of these cells compared to pure alginate microcapsules, which were found to be enhanced by increasing SPI content. Higher degradation profile of different compositions of Alg/SPI microcapsules compared to Alg microcapsules could be the reason for cell elongation and cell proliferation. In this research project two different techniques were considered to produce 3D SPI based scaffolds: electrospinning and bioplotting. The parameters for electrospinning SPI based fibrous scaffold were optimized and then scaffolds were characterized in terms of pore size, fiber diameter, porosity and mechanical properties. The effect of relative humidity on the fibers morphology was investigated. A preliminary cell biology study was carried out to assess the viability of MEF cells in contact with electrospun fibrous scaffolds. The results indicated no toxic effect compared to the control and these fibrous scaffolds were shown to support cell proliferation. Biofabrication of Alg/SPI hydrogels containing MEF cells was investigated to obtain 3D Alg/SPI constructs. Cell viability results were equivalent to the results obtained with capsules. Overall, the outcomes of these studies make the developed materials as promising candidates for applications in soft tissue engineering and wound healing applications and warrant further in vitro and in vivo investigations.; Biomaterialien, synthetischen oder natürlichen Ursprungs, werden bei der Gewebezüchtung für die regenerativen Medizin als sog. Stützstrukturen für Zellen eingesetzt, um das Wachstum und das Differenzieren von Stammzellen zu unterstützen und um letztlich die Funktion des verletzten Gewebes wiederherzustellen. Verschiedene Biomaterialien, die bereits als Stützstrukturen eingesetzt wurden, zeigten jedoch nachteilige Eigenschaften wie fehlende Biokompatibität oder unzureichende Abbaubarkeit. Mit dem Ziel einige diese Nachteile zu überwinden, wie beispielsweise unerwünschte Degradationsprodukte, Inaktivität, oder vielmehr potentielle Biokompatibilitätsprobleme bei Proteinen tierischen Ursprungs, welche Immunogenizität hervorrufen können -, wurde Soja Protein Isolat (SPI) als ein reichlich vorhandenes Protein natürlichen Ursprungs in unterschiedlichen Strukturen für die Weichgewebezüchtung und als Wundversorgung untersucht. Kompositfilme aus SPI und bioaktiven Glass (BG), zeigten hämostatisches Potenzial, welches wichtig für die Anwendung in der Wundversorgung ist. Des Weiteren bestätigten in vitro Studien, das die Adhäsion, Spreitung und Proliferation von embrionalen Maus Fibroblasten (MEF) auf den Kompositfilmen, speziell für SPI Filme, welche 13-93 BG beinhalteten ansteigt. Dies kann u.a. auf die Oberflächenmorphologie dieser Filme zurückgeführt werden. Um SPI basierte Hydrogele für andere Wundtypen, wie z.B. auf Diabetis verursachte Geschwüre oder auf Verbrennungswunden anwenden zu können, wurde SPI mit Alginat kombiniert Alginat (Alg) , welches seit Jahrzehnten ein bekanntes Hydrogel in der Wundversorgung ist, weist einige Nachteile auf, wie eine langsame und nicht kontrollierbare Degradationsrate sowie geringe Zelladhäsionseigenschaften, welche in der vorliegenden Studie durch die Beimischung von SPI gelöst wurden. Zytokompatibilitätuntersuchungen auf Alg/SPI Hydrogelen in 2D zeigten eine verbesserte Zelladhäsion und Proliferation sowohl von humanen Endothelzellen aus der Nabelschnurvene (HUVEC) als auch von humanen dermalen Fibroblasten (NHDF) im Vergleich zu puren Alginat Hydrogelfilmen. Die Zugabe von BG förderte ebenfalls die Zelladhäsion und Proliferation, die auf Veränderungen in der Oberflächenmorphologie der Hydrogele und ionischen Lösungsprodukten des BG zurückzuführen sein könnten. Untersuchungen mittels Nanoindentierung zeigten einen höheren effektiven Elastizitätsmodul von Alg/SPI-Hydrogel-Filmen im Vergleich zu reinen Alg-Hydrogel-Filmen. Humane mesenchymale Stammzellen adipösen Ursprungs (hADSCs), welche in Alg/SPI-Hydrogel-Mikrokapseln als 3D-Zellkulturmodellimmobilisiert wurde, zeigten eine erhöhte Migration und Proliferation im Vergleich zu den immobilisierten Zellen in reinen Alg-Mikrokapseln. Dieses Verhalten der Zellen wurde durch eine Erhöhung des SPI Anteils noch verstärkt. Eine höhere Degradationsrate von Alg/SPI-Mikrokapseln im Vergleich zu Alg-Mikrokapseln, könnte eine Erklärung für die Zunahme der Zellausdehnung und Zellproliferation sein.In dieser Arbeit wurden zwei verschiedene Techniken eingesetzt, um 3D SPI-basierte Konstrukte herzustellen: Elektrospinning und Bioplotting. Die Parameter für das Elektrospinnen von SPI-basierten Fasergerüsten wurden hinsichtlich Porengröße, Faserdurchmesser, Porosität und mechanischen Eigenschaften evaluiert. Zusätzlich wurde die Wirkung von relativer Feuchtigkeit auf die Fasermorphologie untersucht. Eine erste zellbiologische Studie wurde durchgeführt, um die Lebensfähigkeit von MEF-Zellen in Kontakt mit elektrogesponnenen Fasergerüsten zu beurteilen. Diese Ergebnisse zeigten keine toxische Wirkung der Scaffolds auf die Zellen im Vergleich zur Kontrollgruppe und es wurde gezeigt, dass die fibrösen Stützstrukturen die Zellproliferation unterstützen. Die Biofabrikation von Alg/SPI-Hydrogelen, welche MEF-Zellen enthielten wurde untersucht, um 3D Alg/SPI Konstrukte zu erhalten. Die Ergebnisse der Zellvitalitätsuntersuchungen waren identisch zu den Ergebnissen aus der Zellverkapselung. Insgesamt, die Resultate dieser Studien zeigen, dass die entwickelten Materialien vielversprechende Kandidaten für Anwendungen in der Weichgewebezüchtung sowie der Wundversorgung sind und rechtfertigen somit weitere in vitro und in vivo Untersuchungen.
Keywords: Soy protein; Wound healing; Soft tissue engineering; Plant derived protein; Biocompatibility

Soy Protein-based composite hydrogels: Physico-chemical characterization and in vitro cytocompatibility - Tansaz, Samira; Singh, Raminder; Cicha, Iwona; Boccaccini, Aldo R. (Polymers, 2018)
Keywords: Tissue engineering; Bioactive glass nanoparticles; Composite hydrogels; Biocompatibility; Soy protein isolate; Human cells

Soy protein isolate/bioactive glass composite membranes: Processing and properties - Tansaz, Samira; Schulte, M.; Kneser, U.; Mohn, D.; Stark, W.; Roether, Judith; Cicha, Iwona; Boccaccini, Aldo R. (European Polymer Journal, 2018)
Keywords: Clotting assay; Cytocompatibility; Bioactive glass; Soy protein isolate; Wound dressing

Soy protein meets bioactive glass: Electrospun composite fibers for tissue engineering applications - Tansaz, Samira; Liverani, Liliana; Vester, Lars; Boccaccini, Aldo R. (Materials Letters, 2017)
Soy protein isolate (SPI) was used to produce electrospun nanofibers, intended for tissue engineering (TE) applications. For the first time electrospun composite fibers have been successfully fabricated by the addition of nano and micron-sized 45S5 bioactive glass (BG) powders to SPI solution. The influence of BG particles on electrospun fiber morphology and mechanical properties was investigated. Optimization of electrospun parameters with focus on environmental factors indicated the need to control humidity for SPI fibers fabrication.
Keywords: Soy protein isolate Electrospinning Bioactive glass Nanofibers Tissue engineering